Lateral parabrachial nucleus and central amygdala in the control of sodium intake - Andrade-Franze, G. M. F. [UNESP]; Andrade, Carina Aparecida Fabrício de [UNESP]; De Luca, L. A. [UNESP]; Paula, Patricia Maria de [UNESP]; Menani, José Vanderlei [UNESP] (Pergamon-Elsevier B.V. Ltd, 2010)
The lateral parabrachial nucleus (LPBN) and the central nucleus of the amygdala (CeA) are important areas for the control of sodium appetite. In the present study we investigated the effects of bilateral lesions of the CeA on the facilitation of water and 0.3 M NaCl intake produced by the blockade of serotonergic mechanisms or activation of alpha(2)-adrenoceptors with bilateral injections of methysergide or moxonidine, respectively, into the LPBN. Male Holtzman rats (n=5-8) with bilateral sham or electrolytic lesions of the CeA (2 mA; 10 s) and stainless steel cannulas implanted bilaterally in the LPBN were used. In sham rats treated with the diuretic furosemide (10 mg/kg b.w.) combined with the angiotensin converting enzyme inhibitor captopril (5 mg/kg b.w) subcutaneously, bilateral injections of moxonidine (0.5 nmol) or methysergide (4 mu g) into the LPBN increased 0.3 M NaCl intake (29.8 +/- 5.1 and 19.5 +/- 3.7 ml/2 h, respectively, versus vehicle: 8.3 +/- 1.4 ml/2 h) and water intake (17.9 +/- 3.7 and 23.3 +/- 2.8 ml/2 h, respectively, versus vehicle: 11.5 +/- 1.6 ml/2 h). Lesions of the CeA (5-18 days) abolished the increase in 0.3 M NaCl and water intake produced by bilateral injections of moxonidine (10.3 +/- 2.8 and 6.8 +/- 2.3 ml/2 h, respectively) and reduced the increase produced by methysergide (13.6 +/- 2.5 and 14.5 +/- 3.2 ml/2 h, respectively) into the LPBN. The present results show that the increase in water and 0.3 M NaCl intake produced by serotonergic blockade and alpha(2)-adrenergic activation in the LPBN depends on the integrity of the CeA, suggesting that facilitatory mechanisms present in the CeA are essential for the increase of water and hypertonic NaCl intake produced by the blockade of the inhibitory mechanisms of the LPBN. (C) 2010 IBRO. Published by Elsevier Ltd. All rights reserved.
Keywords: sodium appetite; parabrachial nucleus; amygdala; thirst; angiotensin II; serotonin